PLANTING VALUE OF ENTERPRENERSIP (CASE STUDY AT STATE PRIMARY SCHOOL MODEL MALANG) - adji, waluyo satrio (Tarbiyah : Jurnal Ilmiah Kependidikan, 2016)
Values are embedded in the golden age will shape the character according to the embedded value. Planning learning on the subjects of Social Sciences about planting entrepreneurial values essential to recognize by the teacher, so that the entrepreneurial character can be created as early as possible. This study aims to (1) determine the values of entrepreneurship is embedded in SD Negeri Malang Model, (2) how to settle them in the Model SD Negeri Malang. This study used a qualitative approach various case studies. Methods of data collection using observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion. Implementing research in SD Negeri Malang Model, because the mission is to make entrepreneurship in schools as a cornerstone of learning, adequate infrastructure, and the achievement of students who achieved both nationally and internationally. The survey results revealed that, (1) the values of entrepreneurship that have been invested in SD Negeri Model Malang is: the value of independent, creative value, value orientation on performance, the value of risk-taking, leadership values, values of hard work, and the value of honest, (2) planting the values of entrepreneurship by integrating the values of entrepreneurship into every subject, extracurricular, self-development and local content. Keywords: entrepreneurial values, social sciences